Combinational effect of chemical treatments on quality of litchi (Litchi chinensis) during storage - DHAMI, K S; SAGAR, V R (The Indian Journal of Agricultural Sciences, 2021)
Attractive red-coloured pericarp is one of the most important factors in the consumer decision to purchase litchi(Litchi chinensis Sonn.). Red colour of the pericarp turns brown within 2-3 days after harvest which reduces themarketability and commercial value of the fruit drastically and finally incurring huge financial losses to growers.This study was carried out to evaluate the possibility of using combinational application of sodium hypochlorite withsodium chlorite and carnauba wax on the quality of harvested litchi during storage (2016â€“17). Postharvest treatmentsincluded sequential dipping in sodium hypochlorite (0.2%) (T1), sodium hypochlorite (0.2%) + sodium chlorite (0.05%) (T2), sodium hypochlorite (0.2%) + carnauba wax (10%) (T3) and untreated (control) (T4). Treated fruit werethen packed inplastic punnets and stored at 2Â°C and 90-95% relative humidity (RH). All the treatments signiï¬cantlyreduced pericarp browning over control. The most remarkable effect was obtained in fruits treated with sodiumhypochlorite (0.2%) in combination with sodium chlorite (0.05%) as evidenced by delayed anthocyanin degradation,lower polyphenol oxidase activity, fruit decay and weight loss. This treatment also maintained better fruit quality asindicated by higher total soluble solids and phenolic content in fruits, thus can be used as a cost-effective method toreduce pericarp browning and prolong marketable life of litchi up to 25 days.